Complexation of Th(IV) with sulfate in aqueous solution at 10–70 °C. (January 2018) - Di Bernardo, Plinio; Endrizzi, Francesco; Melchior, Andrea; Zhang, Zhicheng; Zanonato, Pier Luigi; Rao, Linfeng
Highlights: Complexation of Th(IV) with sulfate is enhanced at higher temperatures. The enhancement is mainly due to increasingly more positive entropy of complexation. Data suggest re-evaluation of the enthalpy of U(IV)/sulfate in the literature. Abstract: The applicability of spectrophotometry or H + -potentiometry to the studies of the complexation of thorium(IV) in aqueous solutions is limited because Th(IV) does not have characteristic optical absorption in UV/Vis/Near IR region and H + -electrode is not sensitive in solutions of high acidity that needs to be maintained to prevent the hydrolysis of Th(IV). In the present work, the technique of calorimetric titration was used to determine the heat of reaction for the complexation of Th(IV) with sulfate in the temperature range of 10–70 °C. The equilibrium constants and enthalpy of complexation were determined simultaneously from the calorimetric data. It was observed that the enthalpy of complexation is endothermic at 10 °C, and become more endothermic as the temperature is increased. Despite of this, the complexes, Th(SO4 ) 2+ and Th(SO4 )2 (aq), become more stable at higher temperatures due to the increasingly more positive entropy of complexation that exceeds the increase of enthalpy. The trends in the stability of sulfate complexes with tetravalent actinides (Th 4+, U 4+, Np 4+, and Pu 4+ ) are discussed in terms of electrostatic interactions that correlate with the ionic radii of the metal cations.